Obstacles Faced by People with Disabilities (PWD) in Higher Education Institutions on the East Coast of Malaysia - Abdul Rahman, Akmal; Che Hasnah Mahmood,; Nursitihazlin Ahmad Termida, (Recent Trends in Civil Engineering and Built Environment, 2025)
People with disabilities (PWD) are a part of society and have the right to equality in terms of rights and opportunities to live their lives like other members of society. Therefore, a rights-based and protective approach must be implemented to ensure the interests and well-being of PWD are safeguarded. One of the main aspects of special education is the provision of adequate facilities. The lack of facilities for PWD in higher education institutions has prevented them from enjoying a comfortable and fulfilling life like other students. The objective of this study is to examine the facility barriers faced by PWD students in higher education institutions (HEIs). Accessibility is an important aspect of the construction industry because emphasizing accessibility can reduce the problems faced by PWD both inside and outside of buildings, whether they are government or private-owned, and so on. Although there are several related acts, they are still insufficient to address the various problems of facility shortages experienced by this group. This study aims to provide PWD with the opportunity to enjoy a more comfortable life and use all the facilities provided like everyone else. This study was conducted at a higher education institution in the East Coast using a qualitative method, specifically in-depth interviews. The results of the study indicate that facilities for PWD in every building are still inadequate and require immediate improvement to enhance the quality of the facilities and ensure the comfort of PWD in receiving quality education.